Typical Scope of the Crime of Feminicide: An Analysis of the Plenary Agreement No. 001-2016 / CJ-116 - Vega Llapapasca, Rafael A. (2018)
This paper seeks to analyse the Plenary Agreement No. 001-2016: Typical occurrences of the crime of femicide, a phenomenon that has scandalized, with justified reason to Peruvian society, but that, despite apparent efforts and communication campaigns and visualization of the facts of violence, this situation is maintained, more cases are coming to light day by day. The author uses figures, makes an analysis of the approaches used for the application of this emergency legislation, makes an analysis of the protected legal right and of the contexts in which the criminal type of feminicide affects. KEYWORDS: femicide, homicide, legal right, gender approach, transitional justice. JEL CODE: K14, B54